Nanocarrier System for Increasing the Therapeutic Efficacy of Oxaliplatin - Alavi, Negin; Rezaei, Majid; Maghami, Parvaneh; Fanipakdel, Azar; Avan, Amir (Current Cancer Drug Targets, 2022)
The application of Oxaliplatin (OxPt) in different malignancies is reported to be accompanied by several side effects, including neuropathy, nausea, vomiting, diarrhea, mouth sores, low blood counts, loss of appetite, etc. The passive or active targeting of different tumors can improve OxPt delivery. Considering the demand for novel systems meant to improve the OxPt efficacy and define the shortcomings, we provided an overview of different approaches regarding the delivery of OxPt. There is an extending body of data that exhibits the value of liposomes and polymer- based drug delivery systems as the most successful systems among the OxPt drug delivery procedures. Several clinical trials have been carried out to investigate the side effects and dose-limiting toxicity of liposomal oxaliplatin, such as the assessment on Safety Study of MBP-426 (Liposomal Oxaliplatin Suspension for Injection) to Treat Advanced or Metastatic Solid Tumors. In addition, several studies indicated the biocompatibility and biodegradability of this product, as well as its option for being fictionalized to derive specialized smart nanosystems for the treatment of cancer. The better delivery of OxPt with weaker side effects could be generated by the exertion of Oxaliplatin, which involves the aggregation of new particles and multifaceted nanocarriers to compose a nanocomposite with both inorganic and organic nanoparticles.
Keywords: nanocarrier